Genetic Mapping and Validation of Loci for Kernel-Related Traits in Wheat (Triticum aestivum L.) - Qu, Xiangru; Liu, Jiajun; Xie, Xinlin; Xu, Qiang; Tang, Huaping; Mu, Yang; Pu, Zhien; Li, Yang; Ma, Jun; Gao, Yutian; Jiang, Qiantao; Liu, Yaxi; et al. (Frontiers in Plant Science, 2021)
Kernel size and weight play a key role in wheat yield. Phenotypic data from six environments and a Wheat55K SNP array-based constructed genetic linkage map from a recombinant inbred line population (RIL) derived from the cross between the wheat line 20828 and the line SY95-71 were used to identify quantitative trait locus (QTL) for kernel length (KL), kernel width (KW), kernel thickness (KT), thousand-kernel weight (TKW), kernel length-width ratio (LWR), kernel size (KS), and factor form density (FFD). The results showed that 65 QTL associated with kernel traits were detected, of which the major QTL QKL.sicau-2SY-1B, QKW.sicau-2SY-6D, QKT.sicau-2SY-2D, and QTKW.sicau-2SY-2D, QLWR.sicau-2SY-6D, QKS.sicau-2SY-1B/2D/6D, QFFD.sicau-2SY-2D controlling KL, KW, KT, TKW, LWR, KS, and FFD, and identified in multiple environments, respectively. They were located on chromosomes 1BL, 2DL, and 6DS and formed three QTL clusters. Comparison of genetic and physical interval suggested that only QKL.sicau-2SY-1B located on chromosome 1BL was likely a novel QTL. A Kompetitive Allele Specific Polymerase chain reaction (KASP) marker, KASP-AX-109379070, closely linked to this novel QTL was developed and used to successfully confirm its effect in two different genetic populations and three variety panels consisting of 272 Chinese wheat landraces, 300 Chinese wheat cultivars most from the Yellow and Huai River Valley wheat region, and 165 Sichuan wheat cultivars. The relationships between kernel traits and other agronomic traits were detected and discussed. A few predicted genes involved in regulation of kernel growth and development were identified in the intervals of these identified major QTL. Taken together, these stable and major QTL provide valuable information for understanding the genetic composition of kernel yield and provide the basis for molecular marker assisted breeding.